Works of Erasmus of Rotterdam in Vilnius University Library - Jovaišaitė, Emilija (Vilnius University Open Series, 2024)
This paper analyses the works of Erasmus of Rotterdam in the collection of Vilnius University Library, printed during the 16th–18th c. Erasmus’ reception in the Grand Duchy of Lithuania remains a largely unexplored topic. Historiography only alludes to specific cases so a broader overview would contribute to a deeper understanding of the developments of the reading society of the Grand Duchy of Lithuania.The aim of this the paper is to provide comprehensive analysis and explore the topics of the variety of titles, geography of Erasmus’ publishing, history of ownership and reading culture. As most of the copies in Lithuania belonged to clergy or religious orders, theologically and philologically themed works were the most popular. Erasmus’ satires were not as numerous but more longevous in terms of popularity. Most of the copies reached Lithuania from German and Dutch printers. Predominantly Catholic ownership in Lithuania resulted in cases of censorship, most of which were relatively mild as compared to other Catholic countries. Marginalia suggest an active and engaging reader.
Keywords: Erasmus of Rotterdam; Vilnius University Library; reading culture; censorship; monastic libraries; Johan Froben; 16th–18th c.